Catalytic activity of human guanylate‐binding protein 1 coupled to the release of structural restraints imposed by the C‐terminal domain. (19th May 2020) - Ince, Semra; Zhang, Ping; Kutsch, Miriam; Krenczyk, Oktavian; Shydlovskyi, Sergii; Herrmann, Christian
Abstract : Human guanylate‐binding protein 1 (hGBP‐1) shows a dimer‐induced acceleration of the GTPase activity yielding GDP as well as GMP. While the head‐to‐head dimerization of the large GTPase (LG) domain is well understood, the role of the rest of the protein, particularly of the GTPase effector domain (GED), in dimerization and GTP hydrolysis is still obscure. In this study, with truncations and point mutations on hGBP‐1 and by means of biochemical and biophysical methods, we demonstrate that the intramolecular communication between the LG domain and the GED (LG:GED) is crucial for protein dimerization and dimer‐stimulated GTP hydrolysis. In the course of GTP binding and γ‐phosphate cleavage, conformational changes within hGBP‐1 are controlled by a chain of amino acids ranging from the region near the nucleotide‐binding pocket to the distant LG:GED interface and lead to the release of the GED from the LG domain. This opening of the structure allows the protein to form GED:GED contacts within the dimer, in addition to the established LG:LG interface. After releasing the cleaved γ‐phosphate, the dimer either dissociates yielding GDP as the final product or it stays dimeric to further cleave the β‐phosphate yielding GMP. The second phosphate cleavage step, that is, the formation of GMP, is even more strongly coupled to structural changes and thus more sensitive to structural restraints imposed by the GED. Altogether, we depict a comprehensive mechanism of GTP hydrolysis catalyzed by hGBP‐1, which provides a detailed molecular understanding of the enzymatic activity connected to large structural rearrangements of the protein. Database: Structural data are available in RCSB Protein Data Bank under the accession numbers: 1F5N, 1DG3, 2B92 . Abstract : The human guanylate‐binding protein 1 acts as a central player in immune response against invading pathogens. Guanine nucleotide binding to this enzyme and catalysis of hydrolysis control massive structural changes important for the biological function. Here, we address the molecular mechanism of the GMP production, which is coupled to structural changes remote from the catalytic site, particularly involving intramolecular communication between the N‐ and C‐terminal parts of the protein.